Perovskite dissolved metal nanoparticle composite material with nanofiber structure, preparation method and application of perovskite dissolved metal nanoparticle composite material in electrocatalytic methane conversion

By using nanofiber structural perovskite effluent metal nanoparticle composite materials as catalysts in SOEC, the activation difficulty and over-oxidation problems of methane conversion into C2 products are solved, and efficient and stable C2 product production is achieved.

CN119913557AActive Publication Date: 2025-05-02TIANJIN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510085117.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-05-02
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The prior art has problems such as difficulty in converting methane into C2 products, high energy consumption, high equipment temperature resistance requirements, and over-oxidation resulting in by-product generation.

Method used

The nanofiber structure perovskite effluent metal nanoparticle composite material was developed as a catalyst, and the composite spinning precursor film was prepared by electrospinning method, and the metal particle-nanofiber oxide interface was formed by high-temperature calcination and reduction, and methane non-oxidation and direct dehydrogenation of proton-conducting SOEC.

Benefits of technology

It improves methane conversion and selectivity of C2 products, reduces over-oxidation, enhances the stability and activity of the catalyst, and achieves efficient production of C2 products at low reaction temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913557A_ABST
    Figure CN119913557A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite dissolved metal nanoparticle composite material with a nanofiber structure, a preparation method of the perovskite dissolved metal nanoparticle composite material and application of the perovskite dissolved metal nanoparticle composite material to electro-catalytic methane conversion. Dissolving out the metal nanoparticle composite material from the perovskite with the nanofiber structure; the molecular formula is Sr < 2 > X < m > Y < n > Mo < q > O < 6 >-BaZr < 0.1 > Ce < 0.7 > Y < 0.2 > O < 3 >, when X is equal to Fe, m is equal to 1.5, and q is equal to 0.5; when X is Mg, m is equal to 1, and q is equal to 1; y is Fe, Co or Ni; 0.1 > = n > = 0.001. Preparing a precursor solution; synthesizing a composite spinning precursor film through an electrostatic spinning method; roasting at high temperature to remove organic components to obtain nanofibers; a firm metal particle-nanofiber oxide interface is formed by reducing dissolved metal nanoparticles. When the catalyst is used for methane non-oxidation direct conversion of a proton conduction type solid oxide electrolytic tank, high C2 yield and better stability can be obtained at normal pressure and low reaction temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic methane conversion, and more specifically to a nanofiber structured perovskite exsolution metal nanoparticle composite material and a preparation method thereof and application thereof in electrocatalytic methane conversion. Background Art

[0002] In today's chemical industry, the importance of C2 products (such as ethane, ethylene, acetylene, etc.) as basic chemical raw materials is self-evident. They are widely used in the production of plastics, synthetic fibers, rubber and many fine chemicals, and are an indispensable part of modern industry. At present, the traditional C2 production method mainly relies on oil and natural gas as raw materials, which are obtained through cracking and other processes. Oil and natural gas are widely available resources around the world, providing sufficient raw material supply for the C2 industry chain. After a long period of development, the production technology has become quite mature and can achieve efficient and stable production. At the same time, the C2 industry chain can produce a variety of downstream products to meet the needs of different fields and has broad application prospects. [1] .

[0003] Due to its strong CH bond, negligible electron affinity, large ionization energy, and low polarizability, methane (CH4) is highly stable and difficult to activate without sufficient energy input. [2] . The goal of activating methane and converting it into more valuable chemicals has long been recognized as an important challenge. Although the oxidative coupling of methane (OCM) production method has the potential to directly generate C2 through the incomplete oxidation of methane and is expected to have good economic benefits, it still has some significant disadvantages in practical applications. Due to the reliance of this production method on high-temperature environments, the energy consumption in the reaction process is increased, and high requirements are placed on the high-temperature resistance of the equipment. While high temperatures are very beneficial to the formation of carbon, the accumulation of carbon on the catalyst surface can lead to problems such as deactivation and loss of C2 selectivity. In addition, due to the presence of oxygen, CH4 is easily over-oxidized to produce by-products such as CO and CO2, which not only reduces the purity and yield of the product, but also increases production costs and environmental pollution risks. [3] .

[0004] Therefore, we propose an innovative approach to circumvent the current limitations of C2 production by switching the petrochemical production model from the widely used thermal to electrocatalytic. We use SOEC for electrochemical nonoxidative dehydrogenation (NDP) of alkanes to co-produce C2 and hydrogen. SOEC consists of a dense proton-conducting electrolyte membrane, a porous cathode support, and a modified porous anode. Alkanes are fed to the anode and electrochemically dehydrogenated to produce C2 products and H when a voltage is applied. + The generated H +The protons are transferred to the cathode through a dense proton-conducting electrolyte, where they combine with electrons to form high-purity hydrogen. The non-oxidative direct dehydrogenation method avoids the intervention of the oxidation reaction and directly obtains the target product through the dehydrogenation process, providing a new approach to solving the above problems. Proton-conducting solid oxide electrolyzers (H-SOECs) have attracted much attention due to their high efficiency, low cost, and unique proton conduction mechanism for converting electricity into fuels and chemicals using renewable electricity. [4] However, its lower operating temperature (400-700°C) compared to conventional oxygen ion conducting solid oxide electrolyzers (O-SOECs) is not conducive to the activation of methane. In addition, the reduction in operating temperature also places more stringent requirements on the electronic conductivity of the anode material.

[0005] Therefore, in response to the above problems, developing high-performance and high-stability methane dehydrogenation catalysts and promoting the practical application of SOEC technology in the production of C2 products are issues that technical personnel in this field urgently need to solve.

[0006] References:

[0007] [1] Song S, Ye L, Xie K. Sr2Fe 1.575 Mo 0.5 O 6-δ Promotes the Conversion ofMethane to Ethylene and Ethane[J].2022,12 (9):822.

[0009] [2]Gerceker D,Motagamwala AH,Rivera-Dones KR,et al.MethaneConversion to Ethylene and Aromatics on PtSnCatalysts[J].ACS Catalysis,2017,7(3):2088.

[0010] [3]Zhu C, Hou S, Hu X, et al. Electrochemical conversion of methane toethylene in a solid oxide electrolyzer[J].

[0011] Nature Communications,2019,10(1):1173.

[0012] [4]Song J,Hei Y,Li C,et al.Dehydrogenation Coupling of Methane UsingCatalyst-Loaded Proton-ConductingPerovskite Hollow Fiber Membranes[J].2022,12(2):191. Summary of the invention

[0013] The present invention aims to solve the technical problems related to the preparation and application of methane conversion catalysts, and provides a nanofiber structure perovskite dissolution metal nanoparticle catalyst and a preparation method thereof, and applies the catalyst to electrocatalytic non-oxidative direct dehydrogenation of methane to produce C2 products. By forming a firm metal particle-nanofiber oxide interface, carbon deposition and particle agglomeration are inhibited, the specific surface area and catalytic active sites are increased, and the methane conversion rate and C2 product selectivity are improved.

[0014] The specific technical solutions of the present invention are as follows:

[0015] Nanofiber structure perovskite dissolution metal nanoparticle composite material; the molecular formula is:

[0016] SxX m Y n Mo q O6-BaZr 0.1 Ce 0.7 Y 0.2 O3, wherein X=Fe, Mg; when X=Fe, m=1.5, q=0.5; when X=Mg, m=1, q=1; Y=Fe, Co, Ni; 0.1≥n≥0.001.

[0017] The method for preparing the nanofiber structured perovskite dissolution metal nanoparticle composite material of the present invention comprises the following steps:

[0018] (1) preparing a precursor solution: weighing a salt solution according to a stoichiometric ratio, dissolving it in a solvent, and adding a polymer to prepare a precursor solution;

[0019] (2) Using an electrospinning method, a 10-20 kV voltage is used to stretch and refine the charged precursor solution in an electric field, and then the solvent evaporates to form a spinning precursor film;

[0020] (3) The obtained precursor film is heated to 800-1200° C. to be calcined to remove organic components, thereby obtaining a nanofiber structured perovskite material;

[0021] (4) Reducing the dissolved metal nanoparticles at a temperature of 700-900°C to form a metal particle-nanofiber oxide interface, thereby obtaining a nanofiber structured perovskite dissolved metal nanoparticle composite material.

[0022] The salt solution in step (1) is a soluble salt such as nitrate, sulfate, carbonate, or hydrochloride.

[0023] The solvent in step (1) is methanol, ethyl acetate, chloroform or N,N-dimethylformamide (DMF).

[0024] The polymer in step (1) is polyethylene terephthalate (PET), polyacrylic acid (PAA) or polyvinyl pyrrolidone (PVP).

[0025] In the step (1), the mass fraction of the metal salt in the precursor solution is 10%-30%, and the mass fraction of the polymer is 5%-10%.

[0026] In the step (2), 10-20 kV is the DC voltage applied between the syringe nozzle and the drum receiver, and the syringe pushing speed is 0.05-0.20 mL h -1 .

[0027] The heating rate in step (3) is 1-5°C min -1 .

[0028] The nanofiber structured perovskite exsolution metal nanoparticle composite material of the present invention is used for electrocatalytic methane conversion.

[0029] The method for electrocatalytic methane conversion comprises the following steps:

[0030] (1) An electrolyte-supported proton-conducting solid oxide half-cell is prepared, and the prepared composite material is brushed onto the half-cell by screen printing, and then calcined to obtain an electrolyte-supported proton-conducting solid oxide cell with a nanofiber structured perovskite as an anode.

[0031] (2) The prepared battery cell is brushed with silver paste and placed in a sealed reactor and sealed with a sealant. The sealed reactor is placed in a furnace filled with argon atmosphere and reduced using H2 at 700-900°C.

[0032] (3) After inert gas purging, the anode side is switched to the reaction gas - methane and nitrogen mixture, and oxygen (O2) is introduced into the other side and a voltage of 0-2V is applied at a temperature of 550-850℃.

[0033] The specific description of the catalyst used for electrocatalytic methane conversion to produce C2 products is as follows:

[0034] Provide a catalyst for electrocatalytic methane conversion to produce C2 products——Sr2X m Y n Mo q O6-BaZr 0.1 Ce 0.7 Y 0.2 O3 (X = Fe, Mg; when X = Fe, m = 1.5, q = 0.5; when X = Mg, m = 1, q = 1; Y = Fe, Co, Ni; 0.1 ≥ n ≥ 0.001) is abbreviated as SXY n M-BZCY.

[0035] The preparation method comprises the following specific steps:

[0036] (1) preparing a precursor solution: weighing a salt solution according to a stoichiometric ratio, dissolving it in a solvent, and adding a polymer to prepare a precursor solution;

[0037] (2) using an electrospinning method to use a 10-20 kV voltage to stretch and refine the charged precursor solution in an electric field, and then volatilize the solvent to form a composite anode spinning precursor film;

[0038] (3) The obtained precursor film is calcined at 800-1200° C. to remove organic components, thereby obtaining a nanofiber structured perovskite anode material;

[0039] (4) The metal nanoparticles are reduced and dissolved at 700-900°C to form a metal particle-nanofiber oxide interface, which is the key to obtaining high catalytic activity and stability for the methane conversion reaction.

[0040] Preferably, in step (1), the corresponding salt solution is a soluble salt such as nitrate, sulfate, carbonate, or hydrochloride.

[0041] Preferably, in step (1), the solvent is methanol, ethyl acetate, chloroform, N,N-dimethylformamide (DMF), etc.

[0042] Preferably, in step (1), the polymer is a high molecular polymer with good solubility and stretchability, such as polyethylene terephthalate (PET), polyacrylic acid (PAA), polyvinyl pyrrolidone (PVP), etc.

[0043] Preferably, in step (1), based on the total amount of the precursor solution, the mass fraction of the metal salt in the total amount of the precursor solution is 10%-30%, and the mass fraction of the polymer in the total amount of the precursor solution is 5%-10%.

[0044] The beneficial effects of adopting the above technical solution are: making the raw materials dissolve evenly and having moderate viscosity.

[0045] Preferably, in step (2), the high voltage is a DC voltage of 10-20 kV applied between the syringe nozzle and the drum receiver, and the syringe pushing speed is controlled to be 0.05-0.20 mL h -1 .

[0046] The beneficial effect of adopting the above technical solution is that the nozzle can stably spray out uniform fibers.

[0047] Preferably, in step (3), the heating rate is 1-5°C min -1 .

[0048] The beneficial effect of adopting this calcination scheme is that the target product with stable phase and good microscopic morphology is obtained without destroying the fiber structure of the material.

[0049] Preferably, in step (4), the reduction temperature is 700-900°C.

[0050] The beneficial effect of adopting this solution is: obtaining well-dispersed, uniform-sized, non-agglomerated dissolution particles without destroying the battery structure.

[0051] A method for catalyzing the conversion of methane into C2 products is provided, comprising the following operations:

[0052] (1) preparing an electrolyte-supported proton-conducting solid oxide half-cell, brushing the prepared composite material on a plate cell by screen printing, and then calcining to obtain an electrolyte-supported proton-conducting solid oxide cell with a nanofiber structured perovskite as an anode;

[0053] (2) The prepared cell is brushed with silver paste and placed in a sealed reactor and sealed with a sealant. The sealed reactor is placed in a furnace filled with argon atmosphere and reduced with H2 at 700-900°C;

[0054] (3) After inert gas purging, the anode side is switched to the reaction gas - methane and nitrogen mixture, and oxygen is introduced into the other side at a temperature of 550-850°C and a voltage of 0-2V is applied.

[0055] Preferably, in step (2), the reduction temperature is 700-900°C.

[0056] The beneficial effect of adopting this solution is: obtaining well-dispersed, uniform-sized, non-agglomerated dissolution particles without destroying the battery structure.

[0057] Furthermore, the principle of the present invention of electrocatalytic methane conversion using nanofiber structured perovskite dissolving metal nanoparticles as catalysts is:

[0058] Methane is catalytically cracked at the anode to generate H +The proton-conducting SOEC pumps H + To the cathode side, promote the forward conversion of methane. Methyl radicals continue to undergo a chain reaction to generate C2 and other products. + Reacts with O2 to generate H2O. 2- Direct reaction, reducing over-oxidation during methane conversion.

[0059] The beneficial effects achieved by the present invention are:

[0060] (1) The present invention prepares SXY with a disordered stacked three-dimensional mesh fiber structure by electrospinning n M-BZCY anode material. SXY n The M phase and BZCY phase are evenly distributed in the composite anode, expanding the three-phase reaction interface and promoting the close combination of the anode and the electrolyte. The disordered stacking of the anode material in the three-dimensional mesh fiber structure greatly increases the porosity, increases the specific surface area and the number of active sites of the anode, and further affects the catalytic performance of methane dehydrogenation.

[0061] (2) The present invention forms a strong metal particle-nanofiber oxide interface through in-situ reduction and dissolution, and uses it to study the non-oxidative direct dehydrogenation of methane in a proton-conducting SOEC. Particle agglomeration and carbon deposition are inhibited, while the catalytic active sites are increased, thereby improving the methane conversion rate and the selectivity of C2 products.

[0062] (3) Proton-conducting SOEC pumps H in the product in a timely manner. + to the cathode side, promoting the forward conversion of methane. 2- Direct reaction, reducing over-oxidation during methane conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 This is a cross-sectional SEM image of the electrolyte-supported single cell sheet prepared in Example 8;

[0064] Figure 2 It is a schematic diagram of the application process;

[0065] Figure 3 is Sr2Fe in Example 8 1.5 Fe 0.001 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 Cross-sectional view of the cell after O3 is used as anode;

[0066] Figure 4 is Sr2Fe in Example 10 1.5 Fe0.075 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 Cross-sectional view of the cell after O3 is used as anode. DETAILED DESCRIPTION

[0067] In order to further illustrate the present invention, the method for electrocatalytically efficiently converting CH4 to C2 using a nanofiber structured perovskite dissolving metal nanoparticle catalyst provided by the present invention is described below in conjunction with an embodiment. The following embodiments are only to enable the professional and technical personnel to understand the present invention more comprehensively. Based on this, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0068] Example 1

[0069] Take 30 mL, i.e. 28.32 g N,N-dimethylformamide (DMF), and weigh 0.885 g Sr(NO3)2, 1.262 g Fe(NO3)3·9H2O, 0.185 g (NH4)6Mo7O in a beaker. 24 ·4H2O, 0.383g Ba(NO3)2, 0.063g Zr(NO3)4, 0.443g Ce(NO3)3·6H2O, 0.112g Y(NO3)3·6H2O were dissolved and then 1.67g polyvinyl pyrrolidone (PVP) was added to DMF. At this time, the mass fraction of metal salt was 10% and the mass fraction of PVP was 5%. Stir at room temperature for 12h to completely dissolve PVP to obtain a metal precursor solution.

[0070] The precursor solution was transferred into a 10 mL plastic syringe, and the distance between the needle and the drum receiver was adjusted to 18 cm, so that the liquid could fly and stretch to form nano-scale fibers. A 10 kV DC voltage was applied between the syringe nozzle and the drum receiver, and the syringe pushing speed was controlled to 0.05 mL h -1 , so that the nozzle ejects fibers. A spinning precursor film can be obtained by continuing to spin stably for about 24 hours.

[0071] The obtained precursor film was naturally dried at room temperature for 5 h and then placed in a muffle furnace at 1 °C min -1 After heating to 800℃ and keeping it for 5h, the organic components were removed to obtain Sr2Fe 1.5 Fe 0.001 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 O3 nanofiber composites.

[0072] Example 2

[0073] Measure 28.32g methanol into a beaker, weigh 0.893g Sr(NO3)2, 1.294g Fe(NO3)3·9H2O, 0.187g (NH4)6Mo7O 24 ·4H2O, 0.389g Ba(NO3)2, 0.064g Zr(NO3)4, 0.451g Ce(NO3)3·6H2O, 0.114g Y(NO3)3·6H2O are dissolved and then 2.2g polyethylene terephthalate (PET) is added to methanol. At this time, the mass fraction of the metal salt is 10%, and the mass fraction of PET is 6.5%. Stir at room temperature for 12 hours to completely dissolve PET to obtain a metal precursor solution.

[0074] The precursor solution was transferred into a 10 mL plastic syringe, and the distance between the needle and the drum receiver was adjusted to 18 cm, so that the liquid could fly and stretch to form nano-scale fibers. A 12 kV DC voltage was applied between the syringe nozzle and the drum receiver, and the syringe pushing speed was controlled to 0.08 mL h -1 , so that the nozzle can stably eject fibers. A spinning precursor film can be obtained by continuing to spin stably for about 24 hours.

[0075] The obtained precursor film was dried naturally at room temperature for 5 h and then placed in a muffle furnace at 2 °C min -1 After heating to 900℃ and keeping it for 5h, the organic components were removed to obtain Sr2Fe 1.5 Fe 0.025 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 O3 nanofiber composites.

[0076] Example 3

[0077] Measure 28.32g of ethyl acetate into a beaker, weigh 0.894g of Sr(NO3)2, 1.316g of Fe(NO3)3·9H2O, and 0.187g of (NH4)6Mo7O 24 ·4H2O, 0.393g Ba(NO3)2, 0.064g Zr(NO3)4, 0.455g Ce(NO3)3·6H2O, 0.115g Y(NO3)3·6H2O were dissolved and then added to polyacrylic acid (PAA) in ethyl acetate. At this time, the mass fraction of metal salt was 10%, and the mass fraction of PAA was 7.3%. Stir at room temperature for 12h to completely dissolve PAA to obtain a metal precursor solution.

[0078] The precursor solution was transferred into a 10 mL plastic syringe, and the distance between the needle and the drum receiver was adjusted to 18 cm, so that the liquid could fly and stretch to form nano-scale fibers. A 14 kV DC voltage was applied between the syringe nozzle and the drum receiver, and the syringe pushing speed was controlled to 0.10 mL h -1 , so that the nozzle can stably eject fibers. A spinning precursor film can be obtained by continuing to spin stably for about 24 hours.

[0079] The obtained precursor film was dried naturally at room temperature for 5 h and then placed in a muffle furnace at 3 °C min -1 After heating to 1000℃ and keeping it for 5h, the organic components were removed to obtain Sr2Fe 1.5 Fe 0.050 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 O3 nanofiber composites.

[0080] Example 4

[0081] Measure 28.32g of chloroform into a beaker, weigh 1.467g of Sr(NO3)2, 2.194g of Fe(NO3)3·9H2O, 0.307g of (NH4)6Mo7O 24 ·4H2O, 0.651g Ba(NO3)2, 0.106g Zr(NO3)4, 0.753g Ce(NO3)3·6H2O, 0.190g Y(NO3)3·6H2O were dissolved, and 3.77g polyvinyl pyrrolidone (PVP) was added to chloroform. At this time, the mass fraction of metal salt was 15%, and the mass fraction of PVP was 10%. Stir at room temperature for 12h to completely dissolve PVP to obtain a metal precursor solution.

[0082] The precursor solution was transferred into a 10 mL plastic syringe, and the distance between the needle and the drum receiver was adjusted to 18 cm, so that the liquid could fly and stretch to form nano-scale fibers. A 15 kV DC voltage was applied between the syringe nozzle and the drum receiver, and the syringe pushing speed was controlled to 0.12 mL h -1 , so that the nozzle can stably eject fibers. A spinning precursor film can be obtained by continuing to spin stably for about 24 hours.

[0083] The obtained precursor film was dried naturally at room temperature for 5 h and then placed in a muffle furnace at 4 °C min -1 After heating to 1100℃ and keeping it for 5h, the organic components were removed to obtain Sr2Fe 1.5 Fe 0.075 Mo 0.5 O6-BaZr 0.1 Ce 0.7Y 0.2 O3 nanofiber composites.

[0084] Example 5

[0085] Measure 28.32g N,N-dimethylformamide (DMF) in a beaker, weigh 2.008g Sr(NO3)2, 3.052g Fe(NO3)3·9H2O, 0.421g (NH4)6Mo7O 24 ·4H2O, 0.899g Ba(NO3)2, 0.147g Zr(NO3)4, 1.041g Ce(NO3)3·6H2O, 0.262g Y(NO3)3·6H2O were dissolved and then 3.0g polyvinylpyrrolidone (PVP) was added to DMF. At this time, the mass fraction of metal salt was 20%, and the mass fraction of PVP was 7.66%. Stir at room temperature for 12h to completely dissolve PVP to obtain a metal precursor solution.

[0086] The precursor solution was transferred into a 10 mL plastic syringe, and the distance between the needle and the drum receiver was adjusted to 18 cm, so that the liquid could fly and stretch to form nano-scale fibers. A 16 kV DC voltage was applied between the syringe nozzle and the drum receiver, and the syringe pushing speed was controlled to 0.14 mL h -1 , so that the nozzle can stably eject fibers. A spinning precursor film can be obtained by continuing to spin stably for about 24 hours.

[0087] The obtained precursor film was naturally dried at room temperature for 5 h and then placed in a muffle furnace at 5 °C min -1 After heating to 1200℃ and keeping it for 5h, the organic components were removed to obtain Sr2Fe 1.5 Fe 0.1 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 O3 nanofiber composites.

[0088] Example 6

[0089] Measure 28.32g N,N-dimethylformamide (DMF) in a beaker, and weigh 2.614g Sr(NO3)2, 1.592g Mg(NO3)2·6H2O, 0.179g Ni(NO3)2·6H2O, 1.096g (NH4)6Mo7O according to the stoichiometric ratio. 24·4H2O, 0.899gBa(NO3)2, 0.147g Zr(NO3)4, 1.041g Ce(NO3)3·6H2O, 0.262g Y(NO3)3·6H2O were dissolved and then 3.0g PVP was added to DMF. At this time, the mass fraction of metal salt was 20%, and the mass fraction of PVP was 7.66%. Stir at room temperature for 12h to completely dissolve PVP to obtain a metal precursor solution.

[0090] The precursor solution was transferred into a plastic syringe, and the distance between the needle and the drum receiver was adjusted to 18 cm, so that the liquid could fly and stretch to form nano-scale fibers. A 16 kV DC voltage was applied between the syringe nozzle and the drum receiver, and the syringe pushing speed was controlled to 0.18 mL h -1 , so that the nozzle can stably eject fibers. A spinning precursor film can be obtained by continuing to spin stably for about 24 hours.

[0091] The obtained precursor film was naturally dried at room temperature for 5 h and then placed in a muffle furnace at 1 °C min -1 After heating to 900℃ and keeping it for 5h, the organic components were removed to obtain Sr2MgNi 0.1 MoO6-BaZr 0.1 Ce 0.7 Y 0.2 O3 nanofiber composites.

[0092] Example 7

[0093] Measure 28.32g N,N-dimethylformamide (DMF) in a beaker, and weigh 2.614g Sr(NO3)2, 1.592g Mg(NO3)2·6H2O, 0.179g Co(NO3)2·6H2O, 1.096g (NH4)6Mo7O according to the stoichiometric ratio. 24 ·4H2O, 0.899gBa(NO3)2, 0.147g Zr(NO3)4, 1.041g Ce(NO3)3·6H2O, 0.262g Y(NO3)3·6H2O were dissolved and then 3.0g PVP was added to DMF. At this time, the mass fraction of metal salt was 20%, and the mass fraction of PVP was 7.66%. Stir at room temperature for 12h to completely dissolve PVP to obtain a metal precursor solution.

[0094] The precursor solution was transferred into a plastic syringe, and the distance between the needle and the drum receiver was adjusted to 18 cm, so that the liquid could fly and stretch to form nano-scale fibers. A 20 kV DC voltage was applied between the syringe nozzle and the drum receiver, and the syringe pushing speed was controlled to 0.20 mL h -1, so that the nozzle can stably eject fibers. A spinning precursor film can be obtained by continuing to spin stably for about 24 hours.

[0095] The obtained precursor film was naturally dried at room temperature for 5 h and then placed in a muffle furnace at 5 °C min -1 After heating to 1200℃ and keeping it for 5h, the organic components were removed to obtain Sr2MgCo 0.1 MoO6-BaZr 0.1 Ce 0.7 Y 0.2 O3 nanofiber composites.

[0096] Example 8

[0097] The composite material Sr2Fe 1.5 Fe 0.001 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 O3 was screen printed on the electrolyte side of the electrolyte-supported proton-conducting solid oxide half-cell through a 100-mesh screen, dried in an oven, and calcined in air at 950°C for 3 h to form Figure 1 In the single cell sheet shown, the anode thickness is about 40 μm and the electrolyte thickness is about 508 μm.

[0098] The silver paste is applied to the surface of the battery cell as the current collecting layer and calcined in air at 400℃ for 1h to obtain the battery structure as shown in the figure. Figure 2 As shown, the sealed reactor was placed in a sealed reactor and sealed with a sealant. The sealed reactor was placed in a reaction furnace filled with argon atmosphere and then heated at 5 °C min -1 Heat to 260℃ and keep warm for 1h. The flow rate on the anode side is 40ml min -1 The temperature was raised to 800℃ for 1h. After the reduction, the temperature was lowered to 700℃. Nitrogen was introduced for half an hour to purge the hydrogen. Then the reaction gas was switched to 10% CH4-90% N2 with a total flow rate of 20ml / min. 20ml / min was introduced into the cathode side. -1 O2, IV and IT curves were obtained using a VersaSTAT3 electrochemical workstation at 700°C. Product analysis was performed using an online gas chromatograph (GC9790Plus, Fuli), and the specific data are shown in Table 1.

[0099] Table 1 Sr2Fe at 700℃ 1.5 Fe 0.001 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2Electrocatalytic methane conversion performance of O3 anode

[0100]

[0101] The cross-sectional view of the battery after application is as follows: Figure 3 As shown in Figure 2, when n = 0.001, the anode dissolves fewer metal particles; after the test, the fiber structure of the anode material in the battery cell remains good, indicating that Sr2Fe 1.5 Fe 0.001 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 The single cell stability of O3 anode is good. With the increase of voltage, the methane conversion rate increases, and the C2 yield and selectivity increase.

[0102] Example 9

[0103] The composite material Sr2Fe 1.5 Fe 0.05 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 O3 was used as the anode using the screen printing method. The anode was printed on the electrolyte side of the electrolyte-supported proton-conducting solid oxide half-cell through a 100-mesh screen. After being placed in an oven for drying, it was calcined at 950°C in air for 3 hours to form a single cell.

[0104] The silver paste was applied to the surface of the cell as the current collecting layer and calcined in air at 400℃ for 1h to obtain Figure 2 The battery structure shown in the figure is placed in a sealed reactor and sealed with a sealant. The sealed reactor is placed in a reactor filled with argon atmosphere and then heated at 5°C min -1 Heat to 260℃ and keep warm for 1h. The flow rate on the anode side is 40ml min -1 The temperature was raised to 800℃ for 1h. After the reduction, the temperature was lowered to 700℃. Nitrogen was introduced for half an hour to purge the hydrogen. Then the reaction gas was switched to 30% CH4-70% N2 with a total flow rate of 20ml / min. 20ml / min was introduced into the cathode side. -1 O2, IV and IT curves were obtained using a VersaSTAT3 electrochemical workstation at 700°C. The product analysis was performed using an online gas chromatograph, and the specific data are shown in Table 2.

[0105] Table 2 Sr2Fe at 700℃ 1.5 Fe 0.05 Mo 0.5 O6-BaZr 0.1 Ce 0.7Y 0.2 Electrocatalytic methane conversion performance of O3 anode

[0106]

[0107] With the increase of the dissolution amount, the number of active sites increased, and the methane conversion rate and selectivity were improved. At a voltage of 2.0 V, the methane conversion rate and C2 selectivity reached 5.51% and 38.58% respectively, and the C2 yield reached 2.19%.

[0108] Example 10

[0109] The composite material Sr2Fe 1.5 Fe 0.075 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 O3 was used as the anode using the screen printing method. The anode was printed on the electrolyte side of the electrolyte-supported proton-conducting solid oxide half-cell through a 100-mesh screen. After being placed in an oven for drying, it was calcined at 950°C in air for 3 hours to form a single cell.

[0110] The silver paste was applied to the surface of the cell as the current collecting layer and calcined in air at 400℃ for 1h to obtain Figure 2 The battery structure shown in the figure is placed in a sealed reactor and sealed with a sealant. The sealed reactor is placed in a reactor filled with argon atmosphere and then heated at 5°C min -1 Heat to 260℃ and keep warm for 1h. The flow rate on the anode side is 40ml min -1 The temperature was raised to 800℃ for 1h. After the reduction, the temperature was lowered to 700℃. Nitrogen was introduced for half an hour to purge the hydrogen. Then the reaction gas was switched to 25% CH4-75% N2 with a total flow rate of 20ml / min. 20ml min was introduced into the cathode side. -1 O2, IV and IT curves were obtained using a VersaSTAT3 electrochemical workstation at 700°C. The product analysis was performed using an online gas chromatograph, and the specific data are shown in Table 3.

[0111] Table 3 Sr2Fe at 700℃ 1.5 Fe 0.075 Mo 0.5 O6-BaZr 0.1 Ce 0.7 Y 0.2 Electrocatalytic methane conversion performance of O3 anode

[0112]

[0113] The cross-sectional view of the battery after application is as follows: Figure 4As shown, it can be found that the fiber structure of the anode material in the cell is well maintained. When n = 0.075, the anode dissolution particles are uniform and of appropriate size, and the C2 yield is the highest, which is 3.46%. Compared with the traditional C2 production method, the nanofiber structure perovskite dissolution metal nanoparticle catalyst inhibits carbon deposition and particle agglomeration by forming a firm metal particle-nanofiber oxide interface, increases the specific surface area and catalytic active sites, and improves the methane conversion rate and C2 product selectivity. After application, the fiber and dissolution conditions remain good, indicating that the single cell with a nanofiber structure perovskite dissolution nanometal particle composite material as the anode has good stability and methane conversion catalytic activity at 700°C.

[0114] The present invention relates to a nanofiber structure perovskite exsolution metal nanoparticle composite material and a preparation method thereof and is used for electrocatalytic methane conversion; a precursor solution is prepared; a composite spinning precursor film is synthesized by an electrostatic spinning method; organic components are removed by high temperature calcination to obtain nanofibers; and a firm metal particle-nanofiber oxide interface is formed by reducing the exsolution metal nanoparticles. The composite material is used for non-oxidative direct conversion of methane in a proton conductive solid oxide electrolytic cell, and a high C2 yield and good stability can be obtained at normal pressure and low reaction temperature.

[0115] The above description of the preferred embodiments of the present invention is not limited to the above specific implementation methods. Under the enlightenment of the present invention, ordinary technicians in this field can also make various forms of improvements and modifications without departing from the scope of protection of the principles of the present invention and the claims, which all belong to the protection scope of the present invention.

Claims

1. A nanofiber structured perovskite exsolution metal nanoparticle composite material; characterized in that: The molecular formula is: SxX m Y n Mo q O6-BaZr 0.1 Ce 0.7 Y 0.2 O3, where X = Fe, Mg; when X = Fe, m = 1.5, q = 0.5; when X = Mg, m=1, q=1; Y=Fe, Co, Ni; 0.1≥n≥0.001。 2. The method for preparing the nanofiber structured perovskite dissolution metal nanoparticle composite material according to claim 1, characterized in that: The steps include: (1) preparing a precursor solution: weighing a salt solution according to a stoichiometric ratio, dissolving it in a solvent, and adding a polymer to prepare a precursor solution; (2) Using an electrospinning method, a 10-20 kV voltage is used to stretch and refine the charged precursor solution in an electric field, and then the solvent evaporates to form a spinning precursor film; (3) The obtained precursor film is heated to 800-1200° C. to be calcined to remove organic components, thereby obtaining a nanofiber structured perovskite material; (4) Reducing the dissolved metal nanoparticles at a temperature of 700-900°C to form a metal particle-nanofiber oxide interface, thereby obtaining a nanofiber structured perovskite dissolved metal nanoparticle composite material.

3. The preparation method according to claim 2, characterized in that: The salt solution in step (1) is nitrate, sulfate, carbonate or hydrochloride.

4. The preparation method according to claim 2, characterized in that: The solvent in step (1) is methanol, ethyl acetate, chloroform or N,N-dimethylformamide.

5. The preparation method according to claim 2, characterized in that: The polymer in step (1) is polyester, polyethylene terephthalate, polyacrylic acid or polyvinyl pyrrolidone.

6. The preparation method according to claim 2, characterized in that: In step (1), the mass fraction of the metal salt in the precursor solution is 10%-30%, and the mass fraction of the polymer is 5%-10%.

7. The preparation method according to claim 2, characterized in that: In step (2), 10-20 kV is the DC voltage applied between the syringe nozzle and the drum receiver, and the syringe push speed is 0.05-0.20 mL h -1 .

8. The preparation method according to claim 2, characterized in that: The heating rate in step (3) is 1-5°C min -1 .

9. The nanofiber structured perovskite exsolution metal nanoparticle composite material as claimed in claim 1 is used for electrocatalytic methane conversion.

10. The method for electrocatalytic methane conversion according to claim 9, characterized in that: The steps include: (1) preparing an electrolyte-supported proton-conducting solid oxide electrolytic cell with the composite material as the anode; (2) Loading the cell into a sealed reactor and sealing it with a sealant, using H2 for reduction and precipitation at 700-900°C; (3) After purging with inert gas, switch to reactive gas and apply a voltage of 0-2V at a temperature of 550-850°C.

Citation Information

Patent Citations

  • Preparation method of nanofiber composite negative electrode of intermediate-temperature solid oxide fuel cell

    CN104659378A

  • Electrode material of reversible solid oxide battery and composite material, preparation method and application thereof

    CN114400332A

  • Method for preparing surface active particle modified perovskite cathode by ion exchange method and application thereof

    CN118910645A

  • Off-axis sputtering deposition for growth of single crystalline films of a broad range of complex materials

    US20160362812A1

  • Method of manufacturing metal oxide gas sensor functionalized by multicomponent alloy nanoparticle-perovskite composite catalyst

    US20220370990A1